2018
DOI: 10.1117/1.jatis.4.4.049005
|View full text |Cite
|
Sign up to set email alerts
|

Advanced wavefront reconstruction methods for segmented Extremely Large Telescope pupils using pyramid sensors

Abstract: The generation of Extremely Large Telescopes (ELTs) with mirror diameters up to 40 m has thick secondary mirror support structures (also known as spider legs), which cause difficulties in the wavefront reconstruction process. These spider legs create areas where the information of the phase is disconnected on the wavefront sensor detector, leading to pupil fragmentation and a loss of data on selected subapertures. The effects on wavefront reconstruction are differential pistons between segmented areas, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…We will come back to this topic including detailed comparisons of pyramid and roof sensor models as basis in the reconstruction approach in an upcoming paper. At present, there already exist several methods that allow for accurate wavefront reconstruction such as MVM based approaches or the P-CuReD algorithm [65] with LE Strehl ratios around 0.89 as summarized in, e.g., [31]. Nevertheless, we want to emphasize the importance of the development of new algorithms since the high reconstruction performance with the linear methods is obtained in undisturbed closed loop AO systems.…”
Section: Discussionmentioning
confidence: 99%
“…We will come back to this topic including detailed comparisons of pyramid and roof sensor models as basis in the reconstruction approach in an upcoming paper. At present, there already exist several methods that allow for accurate wavefront reconstruction such as MVM based approaches or the P-CuReD algorithm [65] with LE Strehl ratios around 0.89 as summarized in, e.g., [31]. Nevertheless, we want to emphasize the importance of the development of new algorithms since the high reconstruction performance with the linear methods is obtained in undisturbed closed loop AO systems.…”
Section: Discussionmentioning
confidence: 99%
“…46 On the ELTs under design, the primary mirrors are so large that they need to be segmented, which poses the key challenge of cophasing the segments in order to produce a single optical surface. Here is another very valuable feature of the pyramid sensor: its ability to sense differential pistons of a segmented mirror, which has been successfully demonstrated in the laboratory, 48 supported by numerical simulations, 49 and validated on sky under seeing-limited conditions. 39 Moreover, it was found that among the available wavefront sensor types, the PWFS takes the most sensitive measurements of differential pistons on the segments.…”
Section: Pyramid Sensor Features Applications and Modern Challengesmentioning
confidence: 91%
“…8,27,[99][100][101][102][103] Furthermore, the modal basis is not as well-suited for pupils with spiders as the zonal approach, which allows significantly more degrees of freedom in the representation of wavefront. 49,69,[104][105][106][107] An alternative-decoupled-approach to AO loop control considers the two steps: wavefront reconstruction and DM fitting, separately and independently. In this situation, wavefront reconstruction can be based on a synthetic calibration (using a numerical implementation of the sensor's forward model) done independently from the shapes a DM can produce.…”
Section: Coupled and Decoupled Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…For several telescope systems the pupil Ω is annular instead of circular since a shade created by the secondary mirror prevents measurements on these areas. Thus, the light in the area of the central obstruction possibly does not produce reliable measurements [20,37,56,69,70]. Hence, the last step is realized as a multiplication with a second characteristic function…”
Section: The Discrete Pyramid Wavefront Sensormentioning
confidence: 99%